2022
DOI: 10.3390/ma15196658
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nd-N/TiO2 Nanoparticles for Photocatalytic and Antioxidant Applications Using Hydrothermal Approach

Abstract: In this study, photocatalysis was employed to degrade a wastewater pollutant (AB-29 dye) under visible light irradiation. For this purpose, nitrogen (N)- and neodymium (Nd)-doped TiO2 nanoparticles were prepared using the simple hydrothermal method. X-ray diffraction (XRD) revealed an anatase phase structure of the Nd-N/TiO2 photocatalyst, whereas properties including the surface morphology, chemical states/electronics structure and optical structure were determined using transmission electron microscopy (TEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…However, the mismatch of charge capacity between cathode and anode films results in poor stability of these ECDs, as evidenced by the tendency toward uneven coloration and bubbles after multiple cycles [ 14 , 15 , 16 , 17 ]. To ensure the practical application of ECDs in smart windows, electronic displays and anti-glare mirrors, further improvement of the cycling performance and stability of the devices remains the main focus of current research [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mismatch of charge capacity between cathode and anode films results in poor stability of these ECDs, as evidenced by the tendency toward uneven coloration and bubbles after multiple cycles [ 14 , 15 , 16 , 17 ]. To ensure the practical application of ECDs in smart windows, electronic displays and anti-glare mirrors, further improvement of the cycling performance and stability of the devices remains the main focus of current research [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The XRD analysis also showed that NiO‐doped Co nanoparticles had smaller grain sizes than undoped NiO nanoparticles, with an average size of 26 nm. Adding cobalt ions resulted in broader Bragg's peak positions and increased peak intensity [35–40]. The formation of new peak positions such as (100), (232), and (103) indicated the presence of face‐centered cubic phases in the NiO‐doped Co nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the PPT powders, produced via molten salt synthesis and characterized with high [Ti 3+ ], can be considered new promising low-cost catalysts of H 2 O 2 decomposition in aqueous solutions and may be recommended for use in the oxidation processes of green chemistry and in the systems generating O 2 with a controlled rate, i.e., for medical purposes (oxy-therapy). The powdered products obtained as a result of the PPT chemical interaction with H 2 O 2 aqueous solutions (peroxide form of potassium polytitanate) have a yellow color and could be potentially considered prospective photocatalysts that can be active in the visible range of solar radiation and could be destined for water purification or antioxidant applications, similar to [ 45 ].…”
Section: Resultsmentioning
confidence: 99%